Mendeleevite-(Nd), (Cs, [])6 ([], Cs)6 ([], K)6 (REE, Ca)30(Si70O175)(OH, H2O, F)35, a new mineral from the Darai-Pioz alkaline massif, Tajikistan. (1st February 2017) - Agakhanov, Atali; Pautov, Leonid; Sokolova, Elena; Hawthorne, Frank; Yu Karpenko, Vladimir; Siidra, Oleg; Garanin, Viktor
Mendeleevite-(Nd), (Cs, )6(, Cs)6(, K)6(REE, Ca)30(Si70O175)(OH, H2O, F)35 is a new mineral from the Darai-Pioz alkaline massif, Tajikistan. Mendeleevite-(Nd) was found in a pectolite aggregate in silexites (quartz-rich rocks) which consist of fine to medium pectolite grains, quartz, aegirine and fluorite, with minor khvorovite, mendeleevite-(Ce), sokolovaite, hyalotekite, orlovite, kirchhoffite, pekovite, neptunite, zeravshanite, senkevichite, nordite-(Nd), alamosite, pyrochlore-group minerals and baratovite. Mendeleevite-(Nd) forms colourless cubic crystals 10–40 μm in size; it has a vitreous lustre and a Mohs hardness of 5–5.5; Dmeas. = 3.20(2) g/cm3, Dcalc. = 3.155 g/cm3. Mendeleevite-(Nd) is optically isotropic, with the refractive index n = 1.582(2). Mendeleevite-(Nd) is cubic, space group Pm3, a = 21.9106(4) Å; Z = 2. The six strongest reflections in the powder X-ray diffraction pattern are [d (Å), I (%), (h k l)] are: 11.01, 100, (0 0 2); 15.63, 55, (0 1 1); 3.47, 42, (2 0 6); 3.099, 42, (3 4 5); 2.192, 42, (0 0 10); 1.819, 41, (3 6 10). Chemical analysis by electron microprobe gave SiO2 42.30, Ce2O3 10.12, La2O3 3.60, Nd2O3 16.19, Pr2O3 2.79, Sm2O3 4.19, Gd2O3 1.69, Eu2O3 0.47, SrO 2.99, CaO 2.20, Cs2O 8.50, K2O 0.85, H2O 3.85, F 1.25, –O = F2 –0.53, sum 100.46 wt.%, with H2O calculated by analogy with mendeleevite-(Ce). The empirical formula based on 210 (O + F) apfu, with F + OH + H2O = 35 pfu, is Cs6 ( 4.20K1.80) 6{[(Nd9.57Ce6.13Sm2.39La2.20Pr1.68Gd0.93Eu0.27)∑23.17(Ca3.90Sr2.87)∑6.77]∑29.940.06}∑30(Si70.03O175)(OH14.47F6.54)∑21.01 (H2O)14, Z = 2. The simplified and ideal formulae are (Cs, )6 (, Cs)6(, K)6 (REE, Ca)30 (Si70O175)(OH, H2O, F)35 and Cs6(REE23Ca7)(Si70O175)(OH, F)19(H2O)16, respectively. The compatibility index (from measured density) = – 0.039 (excellent). Mendeleevite-(Nd) is a Nd analogue of mendeleevite-(Ce), (Cs, )6(, Cs)6(, K)6(REE, Ca, )30(Si70O175)(H2O, OH, F, )35. Both minerals are named after Dmitri Mendeleev (1834–1907), the great Russian chemist, author of the periodic table of chemical elements, who has had a significant impact on the development of natural sciences and industry, both in Russia and around the world.